Legal Regulation of Perishable Foodstuffs Transportation - YANOVYTSKA, Anna; YANOVYTSKA, Halyna (Journal of Advanced Research in Law and Economics; Vol 10 No 7 (2019): JARLE Volume X Issue 7(45) Winter 2019, 2019)
One of the important areas of development of the state and private economic situation is international trade. Such trade depends on international treaties, the functioning of transport. The article is devoted to the research of legal regulation of carriage of perishable foodstuffs by road. The problems of application of international conventions (CMR and ATP) and other regulatory acts to such transportation are identified. Possible ways of solving such problems concerning transportation within the country and abroad are suggested. To conduct this study, methods of logical analysis, dogmatic analysis, the historical and legal method, and the method of systematic structural analysis are used. As a result of the study, a system of international transportation of perishable food products was presented, prospects, trends and key areas for improving international trade agreements were identified.